KARAKTERISTIK TATA KELOLA SEBAGAI STIMULUS MANAJAMEN PAJAK - Wahidatul Husnaini; Susi Retna Cahyaningtyas; Sapto Hendri BS; Rahmi Sri Ramadhani; Indria Puspitasari Lenap (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2018)
This study aims to examine the characteristics of governance as a stimulus of tax management. The sample of this study is all non-banking and finance companies that included in the Top 50 Publicly Listed Companies - Indonesia based on ASEAN version of Corporate Governance Scorecard and did not experience losses from 2015 – 2016. Based on those predetermined criteria, the study obtained 16 companies as sample of the study. The test results showed that only ETR and previous year Cash ETR had positive effect on tax management. Meanwhile, other variables sucha s coporate governance, the number of directors, the number of independent directors, the remuneration of the executive board and the BTD of the previous year were found to have no effect on tax management. Governance does not affect tax management due to corporate governance in Indonesia is still low so it needs improvement especially protection of shareholders